(untitled) (Scientia Agropecuaria, 2017)
The influence of sex-related chromosomal arrangement in an YY and XY population of Oreochromis niloticus males was investigated in this study. A better spermatic mobility, motility, viability, confluence and less abnormality were found in double Y-chromosome males (YY-males), compared to XY-males; however, this better spermatic quality did not correlate with the body weight of individuals which was significantly better in XY-males. This study establishes the influence of YY-related sequences over spermatic quality and indicates the usefulness of the YY technology as a strategy to obtain better fish breeders and genetically male individuals for a tilapia farming program.